Sexual behaviour, STI knowledge and Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) prevalence in an asymptomatic cohort in Ruhr‐area, Germany: PreYoungGo study. (29th October 2020) - Skaletz‐Rorowski, A.; Potthoff, A.; Nambiar, S.; Wach, J.; Kayser, A.; Kasper, A.; Brockmeyer, N.H.
Abstract: Background and objectives: STIs present a significant threat to individual and public health, disproportionately affecting youth. The study aimed to evaluate (a) the prevalence of asymptomatic Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections among youth using a rapid assay platform, (b) the participants' sexual behaviour and STI knowledge, (c) the utility of the rapid assay in reducing diagnosis‐to‐treatment time. Methods: In this study, 272 subjects (14–31 years) were included between 12/2016 and 7/2018. A questionnaire was used to collect sociodemographic data, sexual behaviour and STI knowledge. Prevalence of CT and NG infections were tested from oral, vaginal and anal swabs for women and oral, anal swabs and urine for men, using the Cepheid Xpert ® CT/NG assay. Time intervals between (i) test to the time the patient were informed of the result (turn around time – TAT) and (ii) test to therapy initiation was documented. Results: Of the 272 subjects (48.9% female, 48.9% male, undisclosed 2.2%), 56.6 % reported university education. 46.6% were men who have sex with men (MSM), and 47.4% of women and 63.1% of men had anal intercourse. 59.9% had previously been tested for HIV, while only 39.7% had for CT, 20.6% for NG. Among these asymptomatic youth 7.7% were positive for CT and 5.5% for NG. The localization of CT were 3.7% genital, 5.5% anal and 2.2% oral, while the corresponding localization of NG were 0.4%, 2.9%, 4.4% respectively. 91.8% of the participants were informed of a positive result within 24 h with a median TAT of 03:09 h. 73.3% initiated therapy within 24 h, with a median time from testing to therapy initiation being 06:50 h. Conclusion: Asypmtomatic CT and NG infections are common and often not tested in persons at risk. The Cepheid Xpert ® CT/NG assay is an effective strategy as it reduces STI diagnosis‐to‐treatment time to less than a day.